PENGARUH ONLINE HANDBOOK EDUCATION TERHADAP KECEMASAN COVID-19 - Sri Mumpuni Yuniarsih; Rahajeng Win Martani (MEDIA ILMU KESEHATAN, 2020)
Background: The rapid increase in the number of new cases of COVID-19 worldwide is making everyone anxious. Anxiety causes a person to respond negatively, so that the individual cannot perform good self-management. Therefore, this problem needs to be resolved, one way to reduce anxiety is to have proper knowledge about COVID-19. Objective: This study aims to identify the effect of online education on COVID-19 anxiety Methods: The method used in this study was a pre-experimental one group pre-post test design using the Hamilton Anxiety Rating Scale (HARS) instrument. Respondents in this study are Indonesian residents who agree to be respondents, aged over 15 years, can access the questionnaire link and participate in all research activities from start to finish. The questionnaire was distributed through the WhatsApp group in the contact of the researcher, the number of respondents who were netted and met the criteria was 93 respondents. The data analysis used was Wilcoxon. Results: The results showed that the pre-test anxiety category was mostly in the mild category, namely as many as 82 respondents (88%). The post-test anxiety category is mostly in the mild category as many as 87 respondents (93.5%). The Wilcoxon test results show that the p value is 0,000 <0.05, which means that there is a significant effect of providing online handbook education on covid-19 anxiety. Conclusion: The better someone's knowledge can reduce the level of anxiety.